Modelling FDI based on a spatially augmented gravity model: Evidence for Central and Eastern European Countries - Markus Leibrecht; Aleksandra Riedl (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
Based on a spatially augmented gravity model the current paper isolates spatial interrelationships in Foreign Direct Investment (FDI) to Central and Eastern European Countries (CEECs) not only across the destination but also across the origin country dimension of FDI. Results show that: (i) spatial interrelationships across destination countries are present and are consistent with the predominance of vertical-complex FDI in total FDI; (ii) spatial correlation across origin countries is given in earlier years of transition, while demonstration and competition effects cancel over the whole sample period; and (iii) agglomeration forces gain in importance for FDI to CEECs.
Keywords: C33; F21; 330; Foreign Direct Investment; Spatial Econometrics; Central and Eastern Europe; Third country effects; Direktinvestition; Raumwirtschaftstheorie; Standort; Gravitationsmodell; Ostmitteleuropa; Osteuropa